PENGARUH FRAUD TRIANGLE TERHADAP POTENSI KECURANGAN LAPORAN KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Rahmadhani, Ayu Dwi; Darmayanti, Novi; Zulkarnaen, Have (E-Jurnal Akuntansi TSM, 2025)
This study aims to analyze the effect of the Fraud Triangle (pressure, Opportunity, and Rationalization) on financial statement fraud, and to examine the moderating role of Good Corporate Governance (GCG). This research was conducted on manufacturing companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) and Bursa Malaysia during the 2021–2024 period. The method used is a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) assisted by SmartPLS software. The results showed that pressure significantly influences financial statement fraud, with a positive direction in Indonesia and a negative direction in Malaysia. Opportunity and Rationalization did not have a significant effect. Furthermore, GCG did not significantly moderate the relationship between pressure and Opportunity toward financial statement fraud in Indonesia. However, GCG significantly moderated the effect of pressure and Rationalization on fraud in Malaysia.